REKONSTRUKSI MAKNA BELAJAR DALAM UPAYA MERESPON PERUBAHAN PARADIGMA PEMBELAJARAN ERA MILENIAL - Rustan Efendy; Bahtiar; Firman (Al-Ishlah: Jurnal Pendidikan Islam, 2018)
This study aims to explore the deconstruction of the meaning of learning by using ascientific approach to learning Arabic in the State Islamic Middle School in MarosRegency. Data collection methods in this study were observation, indepthinterviews and document analysis by using the analytical techniques version ofMiles and Huberman. The results of the study indicate that; Deconstruction of themeaning of learning occurs in Arabic subjects or at least attempts to reconstruct themeaning of learning from the old paradigm to the new paradigm. The old paradigmin question is from students being told to find out, from teachers as the main sourceto multiple sources or various sources, from textual learning to scientificapproaches, from content-based learning to competency-based learning, frompartial learning to integrated learning, from learning a single answer to multidimensionalanswers, from verbalism learning to applicative learning, the use of ascientific approach in learning Arabic can be seen in the learning process using the5 M principle as a strategy or the way a teacher activates his students in thelearning process. 5 M stands for asking, trying, reasoning, communicating andcreating. Its implementation in learning Arabic, teachers stimulate students to ventthemselves by asking questions, trying new things, using reason in analyzing andconcluding learning, communicating ideas and ideas through coversation methodsand creating new paragraphs from a collection of vocabulary or vocabularypreviously mastered and there are technical constraints in order to maximize effortsto deconstruct the meaning of learning including: Arabic language teachers havenot comprehensively understood the meaning of learning and scientific approachesthat apply to all subjects, there is not sufficient training from Arabic teachers sothat their knowledge of the meaning of learning and scientific approaches areobtained from colleagues and information from social media and the internet,moral and material support from the Ministry of Religion, especially the Ministryof Religion of Maros district in the implementation of 2013 Curriculum for ArabicLanguage at State Islamic Middle School.